The Devastating Consequences of Environmental Pollution on Human Health (British Journal of Multidisciplinary and Advanced Studies, 2025)
Environmental pollution is a growing global concern with significant implications for human health. This paper examines the various types of pollution air, water, soil, and noise and their detrimental effects on human well-being. Exposure to pollutants such as particulate matter, toxic chemicals, and heavy metals has been linked to a wide range of health issues, including respiratory diseases, cardiovascular problems, cancer, neurological disorders, and reproductive health concerns. The paper explores the challenges associated with addressing pollution, including the complexity of pollution sources, lack of adequate regulation, and the socioeconomic factors that exacerbate vulnerability. Furthermore, it discusses the long-term consequences of environmental degradation, emphasizing the need for urgent action to mitigate pollution through policy interventions, technological innovation, and public awareness. The impact of environmental pollution on human health underscores the importance of a comprehensive approach to environmental protection and sustainable development.